Taurine as an Essential Neuromodulator during Perinatal Cortical Development - Kilb, Werner; Fukuda, Atsuo (Frontiers in Cellular Neuroscience, 2017)
A variety of experimental studies demonstrated that neurotransmitters are an important factor for the development of the central nervous system, affecting neurodevelopmental events like neurogenesis, neuronal migration, programmed cell death, and differentiation. While the role of the classical neurotransmitters glutamate and gamma-aminobutyric acid (GABA) on neuronal development is well established, the aminosulfonic acid taurine has also been considered as possible neuromodulator during early neuronal development. The purpose of the present review article is to summarize the properties of taurine as neuromodulator in detail, focusing on the direct involvement of taurine on various neurodevelopmental events and the regulation of neuronal activity during early developmental epochs. The current knowledge is that taurine lacks a synaptic release mechanism but is released by volume-sensitive organic anion channels and/or a reversal of the taurine transporter. Extracellular taurine affects neurons and neuronal progenitor cells mainly via glycine, GABA(A), and GABA(B) receptors with considerable receptor and subtype-specific affinities. Taurine has been shown to directly influence neurogenesis in vitro as well as neuronal migration in vitro and in vivo. It provides a depolarizing signal for a variety of neuronal population in the immature central nervous system, thereby directly influencing neuronal activity. While in the neocortex, taurine probably enhance neuronal activity, in the immature hippocampus, a tonic taurinergic tone might be necessary to attenuate activity. In summary, taurine must be considered as an essential modulator of neurodevelopmental events, and possible adverse consequences on fetal and/or early postnatal development should be evaluated for pharmacological therapies affecting taurinergic functions.